ANALISIS KETERAMPILAN PROSES SAINS SISWA MENGGUNAKAN VIRTUAL LABORATORY PHYSICS EDUCATION TECHNOLOGY (PhET) PADA MATERI INDIKATOR ASAM BASA: VIRTUAL LABORATORY PHYSICS EDUCATION TECHNOLOGY (PhET) - Lisa Utami; Raysha Adilla (Journal of Research and Education Chemistry, 2022)
This research was instigated by learning activities that were not maximum because COVID-19 pandemic, so it was difficult to measure student scientific process skills at Vocational High School of Abdurrab Pekanbaru maximally. This research aimed at knowing student scientific process skills using Physics Education Technology (PhET)Virtual Laboratory on Acid Base Indicator lesson. Quantitative descriptive method was used in this research. Observation sheet, posttest question in the form of essay, and student interview as the supporting instrument were used to measure student scientific process skills. The subjects of this research were the tenth-grade students of TLM at Vocational High School of Abdurrab Pekanbaru, and the objects were student scientific process skills using PhET Virtual Laboratory on Acid Base Indicator lesson at Vocational High School of Abdurrab Pekanbaru. The samples were 20 of the tenth-grade students of TLM 3 at Vocational High School of Abdurrab Pekanbaru selected by using purposive sampling technique. Based on the data obtained, it could be concluded that student scientific process skills using PhET Virtual Laboratory overall were on good category. The highest percentage result of scientific process skills was on the aspect of doing an experiment 97.5%, and the lowest result was on the aspect of grouping skill 82.5%.